Spatial spill-overs, structural transformation and economic growth in India - Jaweriah Hazrana; Pratap S Birthal; Digvijay S Negi; Gyanendra Mani; Ghanshyam Pandey (Agricultural Economics Research Review, 2023)
Using a panel of highly spatially disaggregated district-level data for the most recent period this paper demonstrates ‘how spatial dimension and structural transformation influence convergence in economic growth in India’. Our findings show an absolute convergence in economic growth across districts, a finding contrary to the widely reported evidence of divergence across states. More importantly, we find strong spatial linkages in economic growth, leading to a significant acceleration in its speed of convergence. Further, structural transformation too influences the speed of convergence via its spill-over effects, but different sectors influence it differently. While, services sector does not have any significant influence on the speed of convergence, agricultural sector generates positive spill-overs, enhancing the speed of convergence. These findings suggest a need to harness the potential growth effects of spatial linkages by investing more in infrastructure, agricultural research, technology dissemination and skill development especially in the lagging regions, and dismantling the regulatory barriers to inter-regional trade and free flow of goods and services, to bridge the regional developmental gaps.